Producing Documentary Film as A Project on Project Based Learning Approach in Improving Critical Thinking - Rizki Dhian Nushur; Diyana Dewie Astutie (Faculty of Social Science, Universitas Negeri Padang, 2021)
Expert says that having a critical thinking enables a person to decide about the right or wrong, so that problems can be handled responsively. Then, education is expected to facilitate students to be able to face and solve various problems agile. The learning approach taken must be able to facilitate students with teaching materials related to their lives, experiences and interests, so that they can relate them to real life. The learning approach that will be examined in this study is the PjBL Approach. This research aims to improve the critical thinking of students as the nation's next generation, so that they are able to face and solve various problems appropriately. The research was taken place in the training class which is held by Aceh Documentary Foundation in Banda Aceh. They have continuosly use this learning approch in their producing documentary film training. Data collection was carried out through observation, interviews, and FGD. Data analysis used in this research is the Miles & Hubermen style, in which activities in the analysis included data reduction, data display, and conclusion drawing / verification. The results of this research showed that the use of PjBL approach was indeed effective in increasing students' critical thinking because they practiced the knowledge they had acquired directly. However, the results obtained by each individual are different; Even though there was an increase in the way they thought, the level of criticism that was obtained by each student was different.